Generation of recombinant Bacillus subtilis expressing Porcine Epidemic Diarrhea Virus (PEDV) S1 protein in vegetative cell - Jorasa, Paradon; Mekvichitsaeng, Phenjun; Maprang Roshorm, Yaowaluck (International Journal of Engineering and Technology, 2018)
Porcine epidemic diarrhea virus (PEDV) is a mucosal (gut surface) pathogen that causes severe diarrhea in piglets; thus, a vaccine capable of inducing gut-mucosal immune response is crucial for controlling PEDV infection. Bacillus subtilis has been considered a choice for vaccine delivery to the gut mucosa. In this study, we aimed to generate recombinant B. subtilis that can produce PEDV S1 protein in vegetative cell. Two promoters, PrrnO and PgsiB-PsecA, were selected for an early and high yield expression of PEDV S1 gene in B. subtilis vegetative cell and germinating spore. Promoters, PrrnO and PgsiB-PsecA, were linked to the 5â€™ end of the fusion gene pgsA-PEDVS1 and the fusion genes were then inserted into plasmid pDG1662. Recombinant B. subtilis strains were generated by integrating the fusion genes into B. subtilis 168 chromosome via double crossover homologous recombination. PCR amplification and amylase activity assay confirmed integration of the fusion genes into B. subtilis chromosome at amyE locus. Expression of the pgsA-PEDVS1 in B. subtilis vegetative cells germinating from spores was then studied at 2, 4, 8 and 16 hours of culture. Tested by western blot analysis, although only cleaved products of PgsA-PEDVS1 protein were observed, expression levels of pgsA-PEDVS1 under the control of both promoters were comparable at all time points. Importantly, PgsA-PEDVS1 protein could be detected as early as 2 hours after spore inoculation in LB medium. This study suggests that both PgsiB-PsecA and PrrnO promoters can be used for efficient production of PEDV S1 in germinating spore and vegetative cell and may be applicable for expression of other heterologous genes in B. subtilis vegetative cell.Â Â